2018
DOI: 10.1021/acs.langmuir.8b01136
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Protein Unfolding Drives Membrane Bending

Abstract: Dynamic modulation of lipid membrane curvature can be achieved by a number of peripheral protein binding mechanisms such as hydrophobic insertion of amphipathic helices and membrane scaffolding. Recently, an alternative mechanism was proposed in which crowding of peripherally bound proteins induces membrane curvature through steric pressure generated by lateral collisions. This effect was enhanced using intrinsically disordered proteins that possess high hydrodynamic radii, prompting us to explore whether memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…4C). Similar to IDRs, unfolding of lipid‐anchored proteins could induce membrane deformations [182]. Anchoring of the folded human serum albumin to the surface of GUVs or liposomes resulted in minor membrane deformations, but enhanced tubulation was induced when the protein was chemically unfolded.…”
Section: Membrane Remodelling and Fissionmentioning
confidence: 99%
“…4C). Similar to IDRs, unfolding of lipid‐anchored proteins could induce membrane deformations [182]. Anchoring of the folded human serum albumin to the surface of GUVs or liposomes resulted in minor membrane deformations, but enhanced tubulation was induced when the protein was chemically unfolded.…”
Section: Membrane Remodelling and Fissionmentioning
confidence: 99%
“…On its own, a bilayer provides a nanometer-length gradient from a polar, aqueous environment at the interface to a nonpolar hydrophobic environment within the membrane center. However, the lipid-centric view of membranes may be too simplistic because in cell membranes, transmembrane proteins make up $50% of the mass, which can significantly alter the bilayer properties (5)(6)(7). In general, residue polarity follows the hydrophilicity of its environment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a novel method to validate the effect of crowding on membrane bending is to increase the protein volume by externally triggering unfolding of domains. Siaw et al [ 41 ] demonstrated how steric pressure could be generated from chemically triggered protein unfolding, as proteins segregated into ordered lipid domains were shown to drive membrane deformation upon protein unfolding. Structural changes of integral proteins and membrane inserted domains are known to play a critical role in shaping membranes, but the work by Siaw et al shows that it is relevant to account for conformational changes in the cytosolic or ectodomains when considering crowding mechanisms.…”
Section: Asymmetric Protein Density Affects Membrane Shape and Bendingmentioning
confidence: 99%